Outlines for Chautauqua demonstrations in domestic science - Fleming, Louise (My University, 1908)
Introduction: General Outline. I – Recipe. 1. Ingredients and directions for mixing. 2. Number served. 3. Cost per recipe. 4. Cost per person. II. Utensils used in each demonstration. III. Supplies for each demonstration. IV. General topics for lecture work.
Citation: Fleming, Louise. Outlines for Chautauqua demonstrations in domestic science. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Chautauqua; Domestic Science; Home Economics; Recipes; Graduating theses; Senior theses; Theses